Effects of submerged convective cooling in the turning of AZ31 magnesium alloy for tool temperature and wear improvement - Zakaria, M.S. (Springer Science and Business Media Deutschland GmbH, 2022)
Low melting point and material adhesion are associated challenges of magnesium alloy, leading to extreme built-up edge (BUE) and built-up layer (BUL) formations during machining process. Dry machining is favorable for machining magnesium alloy. However, this strategy inflicts excessive adhesive wear on the cutting tool. Therefore, this current work focuses on application of an innovative cooling technique, known as submerged convective cooling (SCC) for the turning of AZ31 magnesium alloy. Prior to cutting experiment, a computational fluid dynamics (CFD) simulation was conducted to evaluate internal structure of cooling module. Based on the CFD simulation, a small inlet/outlet diameter of 3Â mm significantly contributed to the reduction of the tool temperature, due to high heat transfer coefficient of cooling fluid in the SCC. From the experimental results obtained, it was evident that SCC at high cooling water flow rate of 130Â mL/min effectively reduced the tool temperature, chip temperature, and tool-chip contact length by approximately 50, 8, and 28, respectively. Consequently, it improved the surface roughness by 37, when compared with the dry cutting condition. Finally, both BUE and BUL were observed in dry and SCC conditions, but the severity of these wear mechanisms improved or decreased remarkably under SCC conditions. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.